The CHARME" Advanced Big Data Training School for Life Sciences": an example of good practices for training on current bioinformatics challenges - Hoang, Yen; Pfeil, Juliane; Zagoršcak, Maja; Y. A. Thieffry , Axel; Zdravevski, Eftim; Ramšak, Živa; Lameski, Petre; Schulze , Sabrina K.; Papakonstantinou , Eleni; Papageorgiou, Louis; Singh, Tarry; Duarte López, Ariel; et al. (My University, 2019)
The CHARME “Advanced Big Data Training School for Life Sciences” took place during 3-7 September 2018, at the Campus Nord of the Technical University of Catalonia (UPC) in Barcelona (ES). The school was organised by the Data Management Group (DAMA) of the UPC in collaboration with EMBnet as a follow-up of the first CHARME-EMBnet “Big Data Training School for Life Sciences”, held in Uppsala, Sweden, in September 2017. The learning objectives of the school were defined and agreed during the CHARME “Think Tank Hackathon” that was held in Ljubljana, Slovenia, in February 2018. This article explains in detail the step forward organisation of the training school, the covered contents and the interaction/relationships that thanks to this school have been established between the trainees, the trainers and the organisers.